EU Legal Landscape and EMCA on Mitigating Abuse by Majority Shareholder(s) in Public Companies: Any Inspiration for Minority Protection in Independent and Privately Held Turkish Anonim Ortaklık? - Onur Görmez (İstanbul Hukuk Mecmuası)
In EU legislation, a general provision regulating abuse by the majority does not exist. Two approaches have been adopted in Member States. One requires both damage to the minority and to the company, named in this work as double-threshold approach, is implemented by eg France; the other deems the damage to the minority sufficient to conclude on the existence of abuse by the majority; this single-threshold approach is implemented by eg Germany and the Nordic countries. The latter approach, which is also set out by the European Model Companies Act (EMCA), provides better protection to minority shareholders, especially those that are locked in an independent and private anonim ortaklık (Turkish public company – briefly AO). Under EU legislation, as stated by the European Court of Justice in the Audiolux ruling, there does not exist an immanent principle of equal treatment of shareholders. Like EMCA, TCC art 357 imposes on company organs the duty of equal treatment of shareholders who are in the same position. With this provision, it can be argued that the singlethreshold approach is the prevalent approach in Turkish law to determine whether the majority has abused its powers. As for the effective remedies to protect the minority against abuse by majority in independent and privately held AO, a sell-out provision, a remedy implemented by the Directive (EU) 2017/1132 for cross-border conversions, mergers, and divisions of limited liability companies, should be introduced, and a modification to Article 531 of TCC on dissolution by just cause should be made, allowing minority shareholders to request directly from the court to exit the company via sale of their shares. EMCA provisions on Sections 11.35 and 11.37 regarding, respectively, the right to sell-out and redemption, and buyout may serve as an inspiration for TCC.